Checklist and prioritization for management of non-native species of phanerogam plants and terrestrial vertebrates in eight protected areas on the Ecuadorian coast - Brunny, Brunny (2021)
Protected areas (PAs) are important tools for biodiversity conservation. In developing countries, incomplete information about the presence of non-native species makes it difficult to develop strategies to manage this threat to biodiversity. Although a list of non-native species for continental Ecuador has recently been published, information on the status of these species in PAs in terms of invasiveness and impacts is scarce. This study presents a method that proposes criteria to prioritize the management of non-native phanerogam plants and terrestrial vertebrate species in eight PAs in the coastal region of Ecuador, based on the minimal information available. The study area covers 79.6% of all coastal PAs. For the non-native species inventory, we collated information from global biodiversity databases, research papers, theses and project repositories from local private and public universities, public institutions, and management plans for the selected PAs. To categorize the monitoring priority of the non-native species from the selected PAs, we used a pipeline scheme based on species invasion risk principles. We registered 78 non-native species within the eight PAs, consisting of 64 phanerogam plants and 14 terrestrial vertebrates. The PA with the highest non-native plant species richness is Manglares Churute Ecological Reserve (ER) with 25 species (39.1%; n = 64). For terrestrial vertebrates, the highest non-native species richness was in Isla Santay National Recreation Area (NRA) (71.4%; n = 14). 15.6% of the phanerogam plants and 78.5% of the terrestrial vertebrates were classified in the high priority category. The majority of non-native plants are categorized as “more studies required”, reflecting the state of art of invasion ecology in this country. This method allowed us to classify the species based on theoretical and occurrence data. It can potentially be replicated throughout the country and used as a rapid assessment method, complemented with specific invasion/impact studies on PAs in Ecuador